Urgency of Menstrual Hygiene Management at School within Child Rights Framework: Case Studies in 6 Schools - Silvia Anastasia Landa; Novika Noerdiyanti (Yayasan Jurnal Perempuan, 2020)
Researches related to Menstrual Hygiene Management (MHM) show that challenges faced by girls related to MHM in schools, such as lack of MHM facilities and information including negative stigma, potentially decrease the fulfillment of girls’ rights to proper education. However, there is no study in Indonesia to explore the implementation of the Menstrual Hygiene Management (MKM) program in schools from the perspective of children’s rights. Therefore, this study examined the implementation of the MHM from thechildren’s rights perspective and explored the importance of affirmative action towards MHM for girls. This research was conducted qualitatively in March 2018, in the West Jakarta Municipality (DKI Jakarta), Nagekeo District (NTT), and North Lombok District (NTB), one elementary school and one middle school in each regency/city, there were a total of six schools.